Sequential administration of vinorelbine plus cisplatin and bevacizumab followed by docetaxel plus gemcitabine and bevacizumab compared to docetaxel plus cisplatin and bevacizumab regimen as first-line therapy for advanced or metastatic non-squamous non-small cell lung cancer: A multicenter randomized phase II trial of the Hellenic Oncology Research Group (HORG). Issue 1 (April 2015) - Kotsakis, A.; Kentepozidis, N.; Emmanouilidis, Ch.; Polyzos, A.; Agelidou, A.; Vaslamatzis, M.; Chandrinos, V.; Agelaki, S.; Vamvakas, L.; Kalbakis, K.; Katsaounis, P.; Stoltidis, D.; et al.
Highlights: Platinum-based chemotherapy is considered the cornerstone of treatment for NSCLC. Bevacizumab with sequential chemotherapy is feasible with manageable toxicity. This regimen in some cases is very active and leads to durable responses. Abstract: Objectives: To compare the activity and tolerance of the consecutive administration of four active chemotherapeutic agents in combination with bevacizumab to a bevacizumab- and platinum-based chemotherapy doublet as front-line treatment in patients with non-squamous NSCLC. Patients and methods: Patients with advanced/metastatic NSCLC, performance status of 0–2 and normal organ function were randomized to receive either 3 cycles every 3 weeks of cisplatin 80 mg/m 2 (day 1), oral vinorelbine 60 mg/m 2 (days 1 and 8) and bevacizumab 15 mg/kg (day 1) every 3 weeks (VCB regimen) followed by 3 cycles of docetaxel (75 mg/m 2, day 1), gemcitabine (1100 mg/m 2, days 1 and 8) and bevacizumab 15 mg/kg (day 1) (DGB regimen) (arm A) or 6 cycles of cisplatin 80 mg/m 2, docetaxel 75 mg/m 2 and bevacizumab 15 mg/kg on day 1 (DCB regimen; arm B) every 3 weeks. Results: Thirty-eight and 39 patients were enrolled in arm A and B, respectively. The study did not meet its primary endpoint since, the ORR was 39.5% (95% CI: 23.9–55.0%; 1CR and 14 PR) and 46.2% (95% CI: 30.5–61.8%; 2 CR and 16 PR) in arm A and B, respectively ( p  = 0.554). There was no significant difference in terms of response duration (7.4 versus 4.7 months in arm A and B, respectively; p  = 0.697), progression-free survival (5.8 versus 5.5 months, respectively; p  = 0.540) and overall survival (16.9 versus 10.9 months; p  = 0.390). No difference was recorded between the two arms regarding the toxicity profile. There were two drug-related deaths in arm B. Conclusion: Sequential therapy of VCB followed by DGB is a feasible and well-tolerated regimen but failed to show any superiority over the standard DCB regimen.